Economy Circular Pengelolaan Sampah Organik Pasar di Peternakan Sapi dari Hulu hingga Hilir (Studi Kasus di Kelompok Tani Sumber Makmur, Gunung Tembak Kota Balikpapan) - Sekar Inggar Rengganis; Noneng Dewi Zannaria; Reno Pratiwi; Ika Bayu Kartikasari; Galuh Boyo Munanto; Evi Oktavia (Fakultas Teknik Universitas Mulawarman, 2023)
Management of market organic waste in Balikpapan City is an important thing to do to reduce the burden on Manggar TPA. Organic waste, especially market organic waste, which continues to increase along with the rapid growth of the population in Balikpapan City as a buffer city for the IKN can increase the risk of environmental pollution and safety. Market organic waste can be used as an alternative feed for cattle and goats and this has been done by the Sumber Makmur Farmer Group, Gunung Tembak, Balikpapan City. In addition to utilizing market organic waste as cattle and goat feed, the Sumber Makmur Farmer Group has also managed cow manure in the form of solid and liquid into solid organic fertilizer and liquid organic fertilizer. Thus there has been a series of Economy circular which can be an alternative in overcoming the problem of market organic waste in the Balikpapan city as well as increasing economic value. The method in this study uses a descriptive-qualitative method with a design action research model or action research by observing directly to obtain information from the object of study. Discussion of this research is divided into 4 parts such us System for Utilizing Market Organic Waste as Cattle and Goat Feed, the system for utilizing solid cow manure, the system for utilizing liquid cow manure, the potential for managing cattle and goat farms based on an economy circular. The results of observations at the Sumber Makmur Farmer Group, Gunung Tembak, Balikpapan City, show that there have been livestock management activities that apply an economy circular from upstream to downstream. Furthermore, it is hoped that further and in-depth research can be carried out in terms of economy circular-based livestock management in the utilization of organic waste as animal feed so that it can provide more comprehensive information to the wider community so that they can implement this system. Keyword: market organic waste, farming, animal feed, economic circular, manure